2017
DOI: 10.1177/2055207617695135
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy, usage and acceptance by general practitioners and patients: exploratory results from a study in the German outpatient sector

Abstract: ObjectiveThe study’s objective was to assess factors contributing to the use of smart devices by general practitioners (GPs) and patients in the health domain, while specifically addressing the situation in Germany, and to determine whether, and if so, how both groups differ in their perceptions of these technologies.MethodsGPs and patients of resident practices in the Hannover region, Germany, were surveyed between April and June 2014. A total of 412 GPs in this region were invited by email to participate via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
3
18
1
Order By: Relevance
“…27 In a survey of 50 general practitioners in Germany, physicians tended to support patients using mobile devices to keep track of medication use, weight, and blood pressure, while they disapproved of patients using mobile devices to look up medical information or assist with self-diagnosing. 28 In a survey of 59 healthcare practitioners' views on directto-consumer mobile teledermoscopy, some respondents noted the advantages of earlier skin cancer detection, but the majority were unsure or unconvinced that these devices should be provided to patients. 29 A study on physicians' perspectives towards mHealth in Turkey revealed that an innovation's perceived serviceability posed the greatest barrier to its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…27 In a survey of 50 general practitioners in Germany, physicians tended to support patients using mobile devices to keep track of medication use, weight, and blood pressure, while they disapproved of patients using mobile devices to look up medical information or assist with self-diagnosing. 28 In a survey of 59 healthcare practitioners' views on directto-consumer mobile teledermoscopy, some respondents noted the advantages of earlier skin cancer detection, but the majority were unsure or unconvinced that these devices should be provided to patients. 29 A study on physicians' perspectives towards mHealth in Turkey revealed that an innovation's perceived serviceability posed the greatest barrier to its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…26 There is, at the same time, growing awareness of the challenges involved in integrating mHealth as a complementary form of healthcare into existing healthcare practices, also as mHealth is still in its relative infancy and its potential is not fully understood or exploited. 23,27–29 Moreover, although it is broadly agreed that all relevant players should be involved throughout the development of a new mHealth technology to maximize its quality and usability, the practical, epistemic and power-related challenges of multidisciplinary and multiperspectival collaboration are recognized. 27,30…”
Section: Introductionmentioning
confidence: 99%
“…The findings also revealed that adoption decisions rely not only on the technical and material factors such as app features and the available infrastructure but also embrace some important social and cultural aspects. For instance, the users’ individual characteristics such as their previous experience with technology generally, and mHealth specifically, may influence their decision to adopt, as reported by other researchers [ 1 , 58 , 101 , 107 , 108 ]. Their attitudes (eg, resistance to change, risk aversion) may also hinder adoption, and comparable findings were described in earlier studies [ 39 , 40 , 82 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 96%